1997
DOI: 10.1073/pnas.94.12.6110
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase II is a selective target of HIV-1 transcriptional inhibitors

Abstract: The identification of cellular factors that are required to complete various steps of the HIV-1 life cycle may lead to the development of new therapeutics. One key step, transcription from the integrated provirus, is inhibited by members of two distinct classes of compounds, the f lavonoids and the benzothiophenes, via an unknown mechanism, possibly involving a cellular factor. A marked specificity toward inhibiting HIV-1 transcription is evidenced by the ability of drug-treated cells to retain their prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 46 publications
7
72
0
Order By: Relevance
“…Recent studies have shown that LY294002 inhibits both PI3-kinase and casein kinase II (Davies et al, 2000). We used apigenin, a casein kinase II inhibitor (Critchfield et al, 1997), to support our conclusion that PI3-kinase is involved in TNFa-induced degradation of ERa. Apigenin failed to inhibit TNFa-induced degradation of ERa in MCF-7 cells ( Figure 4D).…”
Section: Phosphatidylinositol-3-kinase Inhibitor Ly294002 Stabilises mentioning
confidence: 56%
“…Recent studies have shown that LY294002 inhibits both PI3-kinase and casein kinase II (Davies et al, 2000). We used apigenin, a casein kinase II inhibitor (Critchfield et al, 1997), to support our conclusion that PI3-kinase is involved in TNFa-induced degradation of ERa. Apigenin failed to inhibit TNFa-induced degradation of ERa in MCF-7 cells ( Figure 4D).…”
Section: Phosphatidylinositol-3-kinase Inhibitor Ly294002 Stabilises mentioning
confidence: 56%
“…CK2 is known to phosphorylate a variety of transcription factors in vivo and in vitro so that their activities are either positively or negatively modulated. The phosphorylation by CK2 can affect transcription factors by changing the DNA-binding activity as it is observed for c-Jun 25 and Sp1, 26 by modulating their transcriptional activities such as for MyoD, 27 HIV-1, 22 or IRF-1, 28 and by affecting protein stability, as observed for IjBa, 29,30 PTEN 31 and connexin 45.6. 32 In this work, by using classical selective inhibitors of this kinase such as apigenin, [33][34][35][36] DRB (5,6-dichloro-1-b-D-ribofuranosylbenzimidazole) 22,37,38 and TBB (4,5,6,7-tetrabromobenzotriazole), [39][40][41] we investigated the effect of hypoxia on CK2 activity and the role that this kinase may play to regulate HIF-1 activity.…”
mentioning
confidence: 97%
“…CK2 has also been described to be overexpressed in cancer cells. 22 The human CK2 is composed of 2 catalytic subunits, a and a 0 , and 2 regulatory b subunits with molecular masses of 43, 38 and 28 kDa, respectively. The heterotetramer holoenzyme exists as a 2 b 2 , aa 0 b 2 , or a 0 2 b 2 tetramers.…”
mentioning
confidence: 99%
“…Given this observation, the HL-60 and OM-10.1 cell lines have been used in several studies that simply aim at examining the levels of CD4, CXCR4, and CCR5 or other surface markers under various cellular physiological conditions and drug treatments [138,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159]. These cells have also been used to screen methodologies or drugs that may inhibit HIV-1 infection or reduce transcriptional activation of the virus [117,[160][161][162][163][164][165][166][167][168][169][170][171][172][173]. These cell lines have also been used in studies of drug toxicity, permeability, and/or effects on cellular activation and differentiation to gain an understanding of what specific drugs might do to cells in the bone marrow [144,154,[174][175][176][177][178][179][180][181][182]…”
Section: Hl-60mentioning
confidence: 99%